Children’s Emotional Development and Its Impact on the Teaching and Learning Process - Carsim Carsim; Nurkhosidah Nurkhosidah; Risna Widiastuti; Siti Marhamah (Journal of Social Work and Science Education, 2026)
This study investigates children’s emotional development and its impact on the teaching and learning process at SD Negeri 11 Selat Penuguan. Employing a qualitative approach with descriptive methods, data were collected through observation, teacher interviews, and documentation from students and class teachers at the school. The findings reveal a varied landscape of emotional development among students. Those with well-managed emotions demonstrating anger control, acceptance of reprimands, and collaborative skills exhibited higher activity, confidence, focus, and motivation in class. Conversely, students struggling with emotional management showed poor concentration, irritability, low self-confidence, and difficulty comprehending material. A key finding highlights the teacher’s pivotal role in fostering emotional growth through empathetic approaches, motivation, and a supportive classroom environment. The novelty of this study lies in its contextualized, qualitative insights into the specific interplay between emotional maturity and classroom dynamics within this Indonesian primary school setting. Practically, it underscores the need for teacher training focused on socio-emotional support strategies to enhance learning effectiveness. This study contributes to the field by reinforcing that emotional development is not separate from academic success but is a foundational component of an effective primary education.